Path dependence as a barrier for 'soft' and 'open' innovation. (21st October 2011) - Remneland-Wikhamn, Björn
Open innovation is a management approach which has started to gain interest in both industry and academia. It has shown possibilities to enhance efficiency, effectiveness and creativity, and successful cases have been presented as role models to follow. This paper argues that mature firms face inevitable organisational challenges when aiming to implement open innovation due to their path-dependent decisions manifested into structures, processes and culture. The case of the Volvo Group indicates a 'liability of oldness' for large, mature corporations with ambitions to move towards 'openness'. Organisations enacting open innovation need to consider the coupling of new learning processes with an active unlearning of obsolete knowledge, as well as a negotiation on what should be materialised into new structures and which previous structures should be dematerialised.